College algebra - Larson, Ron (Houghton Mifflin, 2007)
This market-leading text continues to provide students and instructors with sound, consistently structured explanations of the mathematical concepts. Designed for a one-term course that prepares students for further study in mathematics, the new Seventh Edition retains the features that have always made College Algebra a complete solution for both students and instructors: interesting applications, pedagogically effective design, and innovative technology combined with an abundance of carefully developed examples and exercises